Risk Reduction of Breast Cancer by Childbirth, Breastfeeding, and Their Interaction in Korean Women: Heterogeneous Effects Across Menopausal Status, Hormone Receptor Status, and Pathological Subtypes - Seok Hun Jeong; Yoonsuk An; Ji-Yeob Choi; Boyoung Park; Daehee Kang; Min Hyuk Lee; Wonshik Han; Dong-Young Noh; Keun-Young Yoo; Sue K. Park (Korean Society for Preventive Medicine, 2017)
Objectives The purpose of this study was to examine the associations of childbirth, breastfeeding, and their interaction with breast cancer (BC) risk reduction, and to evaluate the heterogeneity in the BC risk reduction effects of these factors by menopause, hormone receptor (HR) status, and pathological subtype. Methods BC patients aged 40+ from the Korean Breast Cancer Registry in 2004-2012 and controls from the Health Examinee cohort participants were included in this study after 1:1 matching (12 889 pairs) by age and enrollment year. BC risk according to childbirth, breastfeeding, and their interaction was calculated in logistic regression models using odds ratios (ORs) and 95% confidence intervals (CIs). Results BC risk decreased with childbirth (3+ childbirths relative to 1 childbirth: OR, 0.66; 95% CI, 0.56 to 0.78 and OR, 0.80; 95% CI, 0.68 to 0.95 in postmenopausal and premenopausal women, respectively); and the degree of risk reduction by the number of children was heterogeneous according to menopausal status (p-heterogeneity=0.04), HR status (p-heterogeneity<0.001), and pathological subtype (p-heterogeneity<0.001); whereas breastfeeding for 1-12 months showed a heterogeneous association with BC risk according to menopausal status, with risk reduction only in premenopausal women (p-heterogeneity<0.05). The combination of 2 more childbirths and breastfeeding for ≥13 months had a much stronger BC risk reduction of 49% (OR, 0.51; 95% CI, 0.45 to 0.58). Conclusions This study suggests that the combination of longer breastfeeding and more childbirths reduces BC risk more strongly, and that women who experience both 2 or more childbirths and breastfeed for ≥13 months can reduce their BC risk by about 50%.